Wright, Z.: Living Knowledge in West African Islam. The Sufi Community of Ibrahim Niasse. - de Diego González, Antonio (THÉMATA. Revista de Filosofía, 2015)
Wright, Z.: Living Knowledge in West African Islam. The Sufi Community of Ibrahim Niasse.